2023
DOI: 10.1021/acs.estlett.2c00826
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Decomposition of Air Pollution Concentrations Highlights Historical Causes for Current Exposure Disparities in the United States

Abstract: Racial–ethnic disparities in exposure to air pollution in the United States (US) are well documented. Studies on the causes of these disparities highlight unequal systems of power and longstanding systemic racismfor example, redlining, white flight, and racial covenantswhich reinforced racial segregation and wealth gaps and which concentrated polluting land uses in communities of color. Our analysis is based on empirical estimates of ambient concentrations for two important pollutants (NO2 and PM2.5). We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…23 Here we find evidence that this phenomenon exists for at-school NO 2 levels in large UAs, accounting for one-quarter of all students enrolled in public schools. Disparities in air pollution exposure by race−ethnicity have many underlying causes, 44 including racist urban planning that results in pollution sources being more likely to be located in black and brown communities. 45 Some causes, such as redlining, 46,47 reflect decisions made many decades ago.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Here we find evidence that this phenomenon exists for at-school NO 2 levels in large UAs, accounting for one-quarter of all students enrolled in public schools. Disparities in air pollution exposure by race−ethnicity have many underlying causes, 44 including racist urban planning that results in pollution sources being more likely to be located in black and brown communities. 45 Some causes, such as redlining, 46,47 reflect decisions made many decades ago.…”
Section: Resultsmentioning
confidence: 99%
“…Disparities in air pollution exposure by race–ethnicity have many underlying causes, including racist urban planning that results in pollution sources being more likely to be located in black and brown communities . Some causes, such as redlining, , reflect decisions made many decades ago.…”
Section: Resultsmentioning
confidence: 99%
“…redlining, eminent domain for freeway/industrial siting, etc) created the foundation for many of these systemic disparities [38,39]. Since the problem is systematic and structured [13,40], solving these aspects will require systematic and targeted intervention. For instance, emission sources are often located in close proximity to neighborhoods with a higher percentage of POC.…”
Section: Discussionmentioning
confidence: 99%
“…While no differences were found between redlined and nonredlined neighborhoods for certain environmental hazards, disparities may still exist. For instance, within the United States, racial–ethnic disparities for air pollution, , chemical toxins, and water quality still persist. Within California, recent research has shown that racially marginalized communities throughout California continue to face disproportionate exposure to oil and gas wells and the associated disturbances, higher levels of water contamination, and lower reductions in PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%